Review of Friction Stir Processing of Aluminium Alloys. (2019) - Kumar, R. Arun; Kumar, R.G. Aakash; Ahamed, K. Anees; Alstyn, B. Denise; Vignesh, V.
Abstract: An advancement to the principles of friction stir welding is the friction stir processing, a technique for modifying the surface, which involves the modification of the local microstructure by refining the microstructure and through localized plastic deformation of the specimen material. The tool that is involved in the process consists of a rotating tool which has a shoulder and pin inserted into the single piece of material. The area which needs to be examined with this process is traversed by this tool in a desired direction. When the shoulder of the tool and the workpiece comes into contact with each other, with the tool traversing at a particular travelling speed and an optimal rotational speed, friction is developed between the two surfaces. This in turn increases the heat of the material to a limit where the material undergoes plastic deformation. Hence when such an exposure occurs localized plastic deformation and the thermal property increase leads to a drastic change in the local microstructure. Various properties have been examined when the material undergoes friction stir processing which involves the production of nanograin, the surface hardness increases followed by the the fatigue strength, wear property and tensile strength of the material. This review paper focuses mainly on the change in microstructure and mechanical properties of Aluminium alloys and their composites and the effect of FSP process through the study of the current trend and the development of FSP to various parameters.